Project-Based Learning untuk Meningkatkan Pemahaman Konsep Zat Aditif pada Siswa Slow Learner di Kelas Inklusif - Selviana Patulen; Aini Mahabbati (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This research aimed to improve the understanding of science concepts in additive materials through the application of Project-Based Learning (PjBL) which is adapted for inclusive learning needs, with a focus on slow learners who tend to experience obstacles in processing abstract information, maintaining attention, and remembering scientific terms, so that it requires concrete, gradual, and contextual learning. The method used is a collaborative Class Action Research (PTK) of the Kemmis and McTaggart model in one cycle which includes the stages of planning, action, observation, and reflection. The main subject of the study was a female student in grade VIII with the initials NA who was identified by the school as having the characteristics of a slow learner. The action was carried out in three meetings through the identification of additives on food and beverage packaging and the preparation of posters. Data was collected using a concept comprehension test of 10 items, observation sheets of student activities, observation sheets of learning implementation, and documentation, which were then analyzed descriptively, quantitatively, and qualitatively. The results showed that the concept comprehension score increased from 65 at pre-action to 80 at the end of Cycle I, exceeding the Minimum Completeness Criteria (KKM) of 75. Student activity reached 83.92%, while the implementation of learning by teachers reached 86.60%. Qualitatively, it was seen that there was an increase in the ability of students to identify the types and functions of additives, distinguish between natural and synthetic additives, explain the impact of their use, and increase the courage in discussing and presenting project results. In conclusion, adaptive PjBL assisted by concrete media, scaffolding, and peer tutors has the potential to support the understanding of the concept of slow learner students in an inclusive classroom. However, generalization of results needs to be done carefully because this study only involves one main subject and one action cycle.  Keywords: Inclusive Classroom, Concept Understanding, Science Learning, Project-Based Learning, Slow Learner